Pemodelan Struktur Dan Mekanisme Interaksi Neuron-Astrocyte Dalam Proses Transfer Informasi Dengan Simulator Brian2 - Hafizhoh, Itsnainiyah; Yuniati, Anis (Sunan Kalijaga Journal of Physics, 2020)
The modeling of neuron-astrocyte interactions in neural networks has been successfully carried out using the Brian2 simulator. The neuron model used is Integrate and Fire, while the astrocyte network model is defined by the Li-Rinzel equation which involves the IP3Rs (q) activation fraction which affects the value of calcium concentration in astrocytes. Interaction modeling between neuron networks and astrocytes involves four types of connections, namely connections between neurons connected by synapses, connections between astrocytes in the form of gap-junction channels (GJCs), synaptic connections to astrocytes and astrocyte connections to synapses. The synaptic connection to the astrocytes is made to trigger the activation of the astrocytes by releasing the neurotransmitter. The astrocyte connection to the synapses is established as a route for the production of the gliotransmitter. The modeling results show that the information transfer mechanism carried out by neurons is in the form of electric current wave propagation, while the information transfer carried out by astrocytes is in the form of calcium wave propagation.